2010
DOI: 10.1134/s1068162010030179
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the oligosaccharide region (core) of the lipopolysaccharides of Shigella flexneri types 2a and 5b

Abstract: The full structure of the lipopolysaccharide core of bacteria Shigella flexneri types 2a and 5b, the causative agents of bacillary dysentery (shigellosis), was established by chemical methods, high-resolution electrospray ionization mass spectrometry, and two-dimensional NMR spectroscopy. The structure of the O-antigen repeating unit and the configuration and position of the linkage between the O-antigen and the core were determined in the lipopolysaccharide of S. flexneri type 2a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Consistent with this proposal, the LPS products of wzy mutants, which contain a single O-repeat unit, are not modified in Salmonella (50,51). Likewise, the first repeat unit of S. flexneri O-antigen is not subject to glucosylation (7,53,54). However, in bacteria producing full-length LPS forms, both glucosylated and nonglycosylated glycans can be produced by the same culture, and when they were separated, the modification was confined to LPS molecules with O-antigens exceeding ϳ6 repeat units in length (55).…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this proposal, the LPS products of wzy mutants, which contain a single O-repeat unit, are not modified in Salmonella (50,51). Likewise, the first repeat unit of S. flexneri O-antigen is not subject to glucosylation (7,53,54). However, in bacteria producing full-length LPS forms, both glucosylated and nonglycosylated glycans can be produced by the same culture, and when they were separated, the modification was confined to LPS molecules with O-antigens exceeding ϳ6 repeat units in length (55).…”
Section: Discussionsupporting
confidence: 64%
“…ESI FT-ICR MS of the oligosaccharides from B16 ( Figure 2B) showed also minor peaks for M + P, M + PEtN, M − P and M − Hex. The M + P compound may represent a variant of 1 with an additional phosphate group on Hep F (GlcN + P + inner core), which has been reported earlier in F2 and F5 (Kondakova et al 2010) and SS (Kübler-Kielb et al 2010). The M + PEtN compound is evidently another variant with a di-PEtN group on Hep E. This conclusion was confirmed by the presence of a major signal at δ P −2.2 ppm for a phosphate group and a minor signal at δ P −9.8 ppm for a diphosphate group in the 31 P NMR spectrum as well as minor signals at δ H 3.29 and δ C 41.6 for NH 2 CH 2 of ethanolamine in the 1 H and 13 C NMR spectra, respectively.…”
Section: Screening Of Oligosaccharide Structures Derived From R-and Ssupporting
confidence: 58%
“…LDHep is a component of the outer core of E. coli K-12 (Müller-Loennies et al 2003) but no DDHep has been hitherto found in the core of the E. coli/Shigella group. Glc L, which bears the DDHep extension in B16, serves also as the site of attachment of the O-antigen to the R3 core in F2 (Kondakova et al 2010;Kübler-Kielb et al 2010). A biological significance of the core extension in B16 remains to be elucidated.…”
Section: Screening Of Oligosaccharide Structures Derived From R-and Smentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, oligosaccharides released from the 2a strains in this work contained high amounts of non-O-acetylated decasaccharides ( Figure 2 e–f). Moreover, minor peaks were detected with masses corresponding to oligosaccharides that lacked one glucose moiety resulting from the glucosylation process of the undecaprenyl pyrophosphate-O-antigen conjugate as non-glucosylated first repeating unit, what provides a measure for the amount of O-antigen chains [ 50 , 51 ]. Thus, oligosaccharide release analysis from strains with serotype Y and 2a O-antigens confirmed that Sf6TSP enzymatic digest is allowed for different degrees of O-acetylation, as naturally found in strains encountered in the field.…”
Section: Resultsmentioning
confidence: 99%